The importance of measuring blood viscosity: challenges and limitations - Huamaní, Charles (2023)
Blood is a mixture of components that has its own identity. One of the physical properties that it acquires is its viscosity, which is the resistance it offers to move. Unlike its components (such as glucose, hemoglobin, cholesterol, etc.), blood does not have a single level of viscosity, but it is variable due to various factors. We present some physical principles that will allow us to better understand these dynamics of blood viscosity, and its possible application in some hemodynamic phenomena, as well as the complexity of its measurement in routine clinical practice.